Relationship between the occlusal plane and three different levels of ala-tragus line in a sample of Sudanese adults. - Mayada Ahmed; Ibrahim Ismail (Universidad de Concepción., 2023)
Aim: Correct orientation of the occlusal plane plays a vital role in achieving the perfect occlusal balance and function of complete dentures. This study aimed to evaluate the most reliable posterior reference point of the ala-tragus line (ATL) concerning occlusal plane (OP) in a sample of the dentate Sudanese population. Materials and Methods: A total of 150 subjects with healthy and well-aligned permanent teeth were randomly selected. Right lateral profile photographs were taken with subjects having a fox plane placed intra-orally, contacting the occlusal plane. Reference points corresponding to inferior, middle, and superior borders of the tragus and inferior border of the ala of the nose were marked on photographs. The angles between the lines were measured using the Auto-CAD software program, and the most parallel relationship was determined. Descriptive statistics in terms of means and standard deviations were presented. Independent t-test and one-way ANOVA tests were used to compare as appropriate. A p-value < 0.05 was considered significant. Results: The mean angle formed by the OP and ATL was 8.5±3.69º for the superior level, 4.68±3.13º for the middle line, and 2.89±2.57º for the inferior line. A significant difference was found between the means of the three angles (p< 0.001), while no significant difference (p> 0.05) was found between both genders regarding the measured angles. Conclusions: The line joining the inferior border of the ala of the nose with the inferior border of the tragus of the ear was the most reliable line in terms of parallelism to determine the occlusal plane orientation.